Infanticide and abortion in early modern Germany - Lewis, Margaret Brannan (The body, gender and culture, 2016)
Introduction -- The baby in the pig sty: defining the crime -- "Such barbarous mothers there are these days:" a growing problem -- Beware the kinderfresser: violence toward children in print culture -- "The child was fresh and perfect:" the influence of experts -- "Sighs of the poor sinner:" sensationalism and enlightenment -- Conclusion